Birds of Tanjung Puting National Park, Kalimantan Tengah. A Preliminary list - Bohap bin Jalan; Birute M. F Galdikas (KUKILA, 1987)
Tanjung Puting National Park is located on the south coast of Kalimantan (Borneo) in the province of Kalimantan Tengah, between 2"35'S and 3° 20'S and 111° 50' and 112° 15'E. Tanjung Puting was first established as a game reserve in two parts during 1936 and 1937 by the Dutch colonial government and the Sultan of Kotawaringin. Consisting of 305,000 ha the reserve was established primarily for the protection of orangutans Pongo pygmaeus, Proboscis Monkeys Nasalls larvatus and rhinoceros Dicerorhinus sumatrensis with the latter, however, becoming extinct in the 1940's due to severe hunting pressure for its horns. Orangutans and proboscis monkeys still remain plentiful. In 1982 the status of Tanjung puting was upgraded to National park.